Matching digital tombstone documentation to unearthed census data: surveying Taiwan's family names, ethnicities and homelands. - Streiter, Oliver; Goudin, Yoann; Huang, Chun (Jimmy); Lin, Ann Meifang (International Journal of Humanities & Arts Computing: A Journal of Digital Humanities, 2012)
In this study we illustrate how data sets, defined and set up independently in digital archive projects, can be linked to mutually enrich each other. The data linked are the digital tombstone archive ThakBong and the visionary use of the 1956 census by Chen and Fried, published in 1968 as 'The Distribution of Family Names in Taiwan'. We explain, through which assumptions the dimensions of the two data sets can be mapped, so that values missing in one set can be completed by the second or, estimated values can be replaced by more reliable values. Conflicting values in both set trigger hypotheses concerning the validity of the data sets.